The innovative university changing the DNA of higher education from the inside out - Christensen, Clayton M.; Eyring, Henry J. (The Jossey-Bass higher and adult education series, 2011)
The Innovative University illustrates how higher education can respond to the forces of disruptive innovation , and offers a nuanced and hopeful analysis of where the traditional university and its traditions have come from and how it needs to change for the future.